Microprocessor-based system for collection and processing of biomedical information - Kaplan, Mikhail; Melnik, Olga; Nikiforov, Mikhael; Ustyukov, Dmitriy; Shulyakov, Andrey (Mediterranean Conference on Embedded Computing (New Jersey. Online), 2021)
Telemedicine elements are being increasingly introduced into all areas of medical care for the population. One of farsighted examples is automated systems for remote pre-trip inspection of drivers. The basis of such systems is a microprocessor-based system for collecting preliminary information received from primary sensors of biomedical information. The paper describes the system created by the authors. The input of this system receives the information about driver's temperature, blood pressure, the presence of alcohol vapors in the exhaled air, the results of the study of tremor, etc. The processed information is transmitted to the doctor on duty's server via a communication channel. The doctor, in turn, makes a decision on the driver's admission to work.